Making a Living between Crises and Ceremonies in Tana Toraja The Practice of Everyday Life of a South Sulawesi Highland Community in Indonesia - de Jong, Edwin B.P (Verhandelingen van het Koninklijk Instituut voor Taal-, Land- en Volkenkunde, 2013)
Making a Living between Crisis and Ceremonies offers an account on the practice of everyday life of the Torajan people both in the highlands of Tana Toraja (South Sulawesi, Indonesia) and elsewhere (Makassar, Jakarta, Maleisië).; Readership: All concerned with the fields of livelihoods, migration, transnationalism, decentralization, economic crisis, and anyone interested in an ethnography of a Southeast Asian highland community: the Toraja.